Peroxisome Proliferator-Activated Receptor Gamma Exacerbates Concanavalin A-Induced Liver Injury via Suppressing the Translocation of NF-κB into the Nucleus. (3rd December 2012) - Ogawa, Yuji; Yoneda, Masato; Tomeno, Wataru; Imajo, Kento; Shinohara, Yoshiyasu; Fujita, Koji; Shibata, Wataru; Kirikoshi, Hiroyuki; Saito, Satoru; Wada, Koichiro; Maeda, Shin; Nakajima, Atsushi
Abstract : Peroxisome proliferator-activated receptor- γ (PPAR γ ) has been reported to reduce inflammation and attenuate fibrosis in the liver. In this study, we investigated the effects of PPAR γ on the liver injury induced by 20 mg/kg Concanavalin A (Con A). The mice were administered one of the three types of PPAR γ ligands (pioglitazone, ciglitazone, and troglitazone) for 1 week, and the serum alanine aminotransferase (ALT) levels at 20 h after Con A injection were significantly elevated in the PPAR γ ligand-treated mice. Furthermore, the serum ALT levels after Con A injection in the PPAR γ hetero-knock-out mice (PPAR γ +/− mice) were lower than those in the wild-type mice (WT mice). Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) revealed extensive liver damage induced by Con A in the pioglitazone-treated mice. Electrophoresis mobility shift assay (EMSA) revealed that activation of translocation of nuclear factor- (NF-) κ B, which is a suppressor of apoptosis, in the nucleus of the hepatocytes was suppressed in the pioglitazone-treated mice after Con A injection. In this study, we showed that PPAR γ exacerbated Con A-induced liver injury via suppressing the translocation of NF- κ B into the nucleus, thereby inhibiting the suppression of liver cell apoptosis.